Belize. Significant achievements 2022 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
The activities carried out by the Belize Delegation of 2022 are identified, focus to needs and interests of the country such as; launched and operationalized a microfinance mechanism/scheme; transforming the classroom-based training program on the use and application of the CCORAL tool into an online course; supported the implementation of various activities in Belize within the framework of the CARICOM Green Climate Fund (GCF); legal recommendations were provided on how to strengthen Belize’s aquatic health regulations in order to meet international standards; implemented a project to promote the consumption of locally produced fruits and vegetables and healthy lifestyles, which was funded by the Canadian Fund for Local Initiatives; and IICA provided the MoAFSE with technical and financial support to initiate germplasm collection for non-traditional fruit trees.